Analysis of Marketing Strategy in Achieving Banking Goals at PT Bank Xyz - Duta Mustajab (Trunojoyo University of Madura, 2022)
This study aims to determine the marketing strategy that has run the company and to determine the relationship marketing strategy through SWOT analysis carried out by the company in relation to the achievement of corporate goals. While the methods of analysis used in this study is an analysis of SWOT analysis is to mngetahui strengths and weaknesses and the opportunities and threats faced by the Bank in the implementation of marketing strategies. Based on the results of the study showed that based on the evaluation of the implementation of the marketing strategy implementation SWOT banking services , especially in the company of PT. Bank Mandiri Branch Makassar, which indicates that the marketing strategies undertaken so far in the marketing of banking services has been able to minimize weaknesses and threats in implementing strategies that have been carried out and in addition the power and opportunities are more prominent when compared to the weaknesses and threats. Based on the results of the SWOT analysis , the strategy is suitable for use in the marketing of banking services at PT. Bank Mandiri Branch Makassar is an aggressive strategy.